2007
DOI: 10.1108/13595474200700028
|View full text |Cite
|
Sign up to set email alerts
|

Staff Support, Staff Stress and Job Satisfaction in Working with People with Learning Disabilities and Challenging Behaviours

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…These results confirmed outcomes of studies conducted within the field of IDs and CB based on smaller sample sizes (e.g. Rose et al 2006;Leyin & Wakerly 2007). With regard to job satisfaction, positive correlations were found for support at work from all four groups of professionals as well as for team climate.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results confirmed outcomes of studies conducted within the field of IDs and CB based on smaller sample sizes (e.g. Rose et al 2006;Leyin & Wakerly 2007). With regard to job satisfaction, positive correlations were found for support at work from all four groups of professionals as well as for team climate.…”
Section: Discussionsupporting
confidence: 83%
“…2021). Previous studies conducted amongst staff have also indicated the important role that other staff members play in the provision of support (Leyin & Wakerly 2007; Judd et al . 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), depression and stress (Gray‐Stanley et al . ; Leyin & Wakerly ) and challenging ethical issues (Wilson et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for people with more significant disabilities who may have the most compromised autonomy of any group (Lakin et al 2008). Support workers, themselves, face challenges that impact their ability to promote autonomy within support services, including: high turnover rates (Larson & Lakin 1999), lack of support workers for hire , inadequate wages (Hewitt et al 2008;Larson & Lakin 1999;Test et al 2003), inadequate training (Test et al 2004), depression and stress (Gray-Stanley et al 2010;Leyin & Wakerly 2007) and challenging ethical issues (Wilson et al 2008). Because support workers are in a unique position to promote or inhibit autonomy (Grimby 2002), these issues also directly impact people with intellectual disability in a way that can potentially diminish their autonomy (Test et al 2003).…”
Section: Introductionmentioning
confidence: 99%